Carbonic anhydrase inhibitors: in vitro inhibition of α isoforms (hCA I, hCA II, bCA III, hCA IV) by flavonoids - Ekinci, Derya; Karagoz, Lutfi; Ekinci, Deniz; Senturk, Murat; Supuran, Claudiu T. (TAYLOR & FRANCIS LTD, 2013)
A series of flavonoids, such as quercetin, catechin, apigenin, luteolin, morin, were investigated for their inhibitory effects against the metalloenzyme carbonic anhydrase (CA). The compounds were tested against four alpha-CA isozymes purified from human and bovine (hCA I, hCA II, bCA III, hCA IV) tissues. The four isozymes showed quite diverse inhibition profiles with these compounds. The flavonoids inhibited hCA I with K-I-s in the range of 2.2-12.8 mu M, hCA II with K-I-s in the range of 0.74-6.2 mu M, bCA III with K-I-s in the range of 2.2-21.3 mu M, and hCA IV with inhibition constants in the range of 4.4-15.7, with an esterase assay using 4-nitrophenyl acetate as substrate. Some simple phenols/sulfonamides were also investigated as standard inhibitors. The flavonoids incorporate phenol moieties which inhibit these CAs through a diverse, not yet determined inhibition mechanism, compared to classic inhibitors such as the sulfonamide/sulfamate ones.
Keywords: Carbonic anhydrase; flavonoid; inhibitor; phenol; ACTIVE-SITE; PURIFICATION; COUMARINS; ISOZYMES; BINDING; Biochemistry & Molecular Biology; Pharmacology & Pharmacy